Effect of Coronary Collateral Circulation on Preoperative and Postoperative QT Dispersion in Patients Undergoing Coronary Artery Bypass Grafting. - Nisanoglu, Vedat; Ozgur, Bulent; Sari, Suleyman; Aldemir, Mustafa; Aksoy, Yuksel; Battaloglu, Bektas; Berat Cihan, Hasan; Yetkin, Ertan; Erdil, Nevzat (Annals of Medical Research, 2021)
None
Keywords: Collateral circulation, Coronary disease, Coronary artery bypass, QT dispersion.